A New Voltage Control Method for Single-Phase PWM Inverters - Dahono, Pekik Argo; Taryana, Een (Journal of Engineering and Technological Sciences, 2011)
A  new  voltage  control  method  for  single-phase  full-bridge PWM inverters  that having an output LC filter  is proposed in this paper. The proposed voltage  controller has a capability to realize a zero steadystate output voltage error with fast response. The zero steady-state output voltage error is achieved by using a controller that is derived by using the virtual LC resonant circuit. Fast response is obtained by using a virtual resistance  that  is  connected  in  parallel  with  the  filter  capacitor.  The validity of the proposed method is verified by experimental results.